The first Italian historical grammar schoolbook: The Appendici to Francesco Zambaldi’s Grammatica Della Lingua Italiana (1905) - Cella, Robert (Kwartalnik Neofilologiczny, 2026)
ABSTRACT This paper analyses the Appendici to Francesco Zambaldi’s Grammatica della lingua italiana (Sonzogno, Milano, 1905), viewed as an original reworking of Die italienische Sprache by Francesco D’Ovidio and Wilhelm Meyer-Lübke (1888) and of Meyer-Lübke’s Italienische Grammatik (1890); they are the first (and probably the only) Italian historical grammar profile for school use.